Relationships between self-regulated and academic performance among graduate students - Zarifah, binti Mos (Universiti Malaysia Sarawak (UNIMAS), 2015)
The purpose of this study was to analyse relationships between self-regulated learning and academic performance among graduate students. Eighty graduate students from the Faculty of Cognitive Sciences and Human Development were randomly recruited whom enrolled in the Learning Sciences Programme and the Human Resources Programme of session 2015/2016. The Motivated Strategies for Learning Questionnaire was administered. The Pearson correlation analysis was explored in data analysis. Two independent variables were motivation and learning strategies and academic performance measured as a dependent variable. Findings showed that there was no relationship between motivation and learning strategies with academic performance. Implication also discussed about why these two independent variables were not affect the dependent variable in this study .